Parents' and child health professionals' attitudes to dietary interventions in autism spectrum disorder: findings from a UK survey. (29th September 2015) - Couteur, AL; Charlton, J; Winburn, E; Cutress, A; Adams, S; McColl, E; McConachie, H; Parr, J; Baird, G; Gringras, P; O'Hare, A; Wilson, DC; et al.
Abstract : A recent Cochrane review highlighted the need for rigorous evaluation of the gluten free casein free (GFCF) diet in autism spectrum disorder (ASD). A multi-site randomised controlled trial (RCT) would require the cooperation of both parents and child health professionals. Aims: To investigate parents' and child health professionals' attitudes towards dietary interventions including the GFCF diet. To assess the feasibility of an RCT of this diet in preschool children with autism, and identify potential barriers and facilitators for successful trial completion. Methods: UK parents of children with ASD and child health professionals were invited to complete a short web-based questionnaire. Results (Findings to Date): 247 of 361 parents and 248 of 317 professionals (of these 42% were paediatricians, 35% child and adolescent psychiatrists; 23% dieticians and "other" professionals) who expressed an interest have completed the relevant versions of the questionnaire. Parents: Just under half (46%) were currently giving their child dietary supplements. 84% were aware of GFCF diet (51% of these had heard about it from other parents). A third were implementing special diets, mainly GFCF (81%), and all but 2 of these families were also using dietary supplements. Three quarters of parents said they would "definitely" take part, or would consider participating in an RCT of GFCF diet. Parents commented that they would be more likely to enrol their child knowing they would have access to a study dietician. Professionals: 50% of all respondents reported they did not know enough about the efficacy of the GFCF diet to advise families and 72% had been approached by parents for advice about this diet. The majority of professionals (94%) strongly supported the need for evaluation of the GFCF diet and 75% would be prepared to recruit children to a future trial. Conclusion: These findings confirm the need to evaluate biomedical interventions such as the GFCF diet. Facilitators and barriers towards recruitment and retention of families for a future RCT have been identified. Professionals and parents have shown support through their preparedness to refer, and willingness to participate.